Frölicher Structures, Diﬃeties, and a Formal Kp Hierarchy - Reyes-Garcia, E (American Mathematical Society, 2023)
We propose a deﬁnition of a diﬃety based on the theory of Frolicher structures. As a consequence, we obtain a natural Vinogradov sequence and, under the assumption of the existence of a suitable derivation on a given diffiety, we can form on it a Kadomtsev-Petviashvili hierarchy which is well-posed. © 2023 American Mathematical Society.